Analisis Pengaruh QRIS terhadap Transaksi UMKM - Fitria; Ismayadi (Yayasan Al Ma'arif Dawuhan, 2025)
The advancement of digital technology and financial technology (fintech) has driven the implementation of the Quick Response Indonesian Standard (QRIS) as a digital payment method. This study aims to analyze the impact of QRIS on the transaction volume of Micro, Small, and Medium Enterprises (MSMEs) in Pati Regency, identify the factors influencing QRIS adoption, and evaluate its contribution to MSME economic growth. A literature review method is employed to examine the effects of QRIS implementation on MSMEs in Pati. Secondary data is collected from various sources, including academic journals, books, research reports, and official publications from relevant institutions. The study applies a qualitative descriptive analysis to interpret the findings. The results indicate that QRIS has a positive and significant impact on the transaction volume of MSMEs in Pati Regency. Furthermore, several factors, such as digital literacy, infrastructure readiness, and customer preference, influence the adoption rate of QRIS among MSMEs. This study recommends that MSMEs enhance their utilization of QRIS to improve financial transactions, while relevant stakeholders should actively promote QRIS adoption through education, training, and incentive programs. Additionally, government policies supporting digital payment systems are essential to fostering MSME growth. Further research is required to explore the broader implications of QRIS adoption, particularly its effects on financial inclusion, business sustainability, and economic resilience within the MSME sector.